Penerapan Teknik Pemodelan Untuk Meningkatkan Kemampuan Berpidato - Siti Kholipah (JURNAL GLOBAL EDUKASI, 2022)
Abstract. Low speech ability is a problem in learning Indonesian. To overcome this, an appropriate strategy is needed, one of which is the application of modeling techniques. Meanwhile, the problem in this research is how to apply modeling techniques in improving the speech ability of class IX-1 students of SMP Negeri 1 Pulo Bandring in the 2021/2022 academic year. Based on the analysis of the previous learning data, the authors see that the students' speaking ability is still low with an average result of 64.70% or 22 students completing and 35.30% or 12 students incomplete. This can be seen from the students' overall speaking ability at the end of the cycle, which is 78.35. In the first cycle, students who have not completed 17.65% and who have completed 82.30% with an average value of 78.08 students' speaking ability with sufficient category. In cycle II, students who have not completed are 02.95% and those who have completed are 97.05% with an average value of 82.79 students' speaking abilities with good categories. From the results of this classroom action research, it can be concluded that the application of modeling techniques can improve students' speaking abilities. Keywords: Speech; Modeling Techniques Abstak.Kemampuan berpidato yang rendah menjadi permasalahan tersendiri dalam pembelajaran Bahasa Indonesia. Untuk mengatasinya diperlukan strategi yang tepat, salah satunya dengan penerapan teknik pemodelan. Adapun, masalah dalam penelitian ini adalah bagaimana penerapan teknik pemodelan dalam meningkatkan kemampuan berpidato siswa kelas IX-1 SMP Negeri 1 Pulo Bandring tahun pelajaran 2021/2022. Berdasarkan analisis data pembelajaran sebelumnya, penulis melihat kemampuan berpidato siswa masih rendah dengan hasil rata-rata siswa yang tuntas 64.70% atau 22 siswa, dan belum tuntas 35.30% atau 12 siswa. Hal ini dapat dilihat dari kemampuan berpidato siswa secara keseluruhan pada akhir siklus yaitu 78.35. Pada siklus I, siswa yang belum tuntas 17.65% dan yang tuntas 82.30% dengan nilai rata-rata kemampuan berpidato siswa 78.08 dengan kategori cukup. Pada siklus II, siswa yang belum tuntas adalah 02.95% dan yang tuntas 97.05% dengan nilai rata-rata kemampuan berpidato siswa 82.79 dengan kategori baik. Dari hasil penelitian tindakan kelas ini dapat disimpulkan bahwa penerapan teknik pemodelan dapat meningkatkan kemampuan berpidato siswa. Kata kunci: pidato; teknik Pemodelan